Evaluation of the Status of Organizational Culture among Hospital Staff in Iran: A Systematic Review and Meta-Analysis. Issue 3 (3rd July 2021) - Jahangiri, Reza; Derakhshani, Naser; Raeissi, Pouran; Alipour, Samira; Ghasemyani, Shabnam
Abstract: organizational culture in health care organizations to improve staff performance and quality of care. This study was conducted as a systematic review meta-analysis. The required data was searched in the databases and search engines between 2000 and 2019. CMA: 2 software was used to perform the meta-analysis. A total of 16 studies were selected for Meta-Analysis. The mean score of organizational culture of hospital staff evaluated by Denison tool was 3.063 and the mean score of organizational culture of hospital staff evaluated by Robbins tool was 2.527. It is essential for hospital managers to create a healthy and creative environment.